Gender Discriminatory Practices in Tamang and Brahmin Communities - Pokharel, Samidha (Tribhuvan University Journal, 2010)
The study documents the discriminatory practices in different ethnic groups. The study was designed as a descriptive study based on sample survey. The total of 200 women including Brahimns and Tamangs were selected randomly for this study. The study findings show that there is discriminatory practice against women in both communities. Women perceive more discrimination at the societal level comparing to household level. With compare to Tamang, Brahmin women experience more discrimination in marriage time and choice of partner. They consider gender and customary practices as major factors responsible for discrimination. Key words: Gender Discriminatory; Tamang; Brahmin Communities Tribhuvan University Journal Volume XXVI No. 1, 2009 Page: 85-98